New Pyridinium Compound from Marine Sediment-Derived Bacterium Bacillus licheniformis S-1 - Han Wang; Yifei Wang; Yanjing Li; Guilin Wang; Ting Shi; Bo Wang (Molecules, 2024)
The structural diversity of marine natural products is considered a potential resource for the pharmaceutical industry. In our study of marine-derived compounds, one bacterium Bacillus licheniformis S-1 was discovered to have the ability to produce bioactive natural products. After a further chemistry investigation, one novel 4-aminopyridinium derivative, 4-(dimethylamino)-1-(2S-((4hydroxybenzoyl)oxy)propyl)pyridin-1-ium (1), along with 15 known cyclic dipeptides (2–16) were isolated from the bacterium B. licheniformis S-1 derived from a shallow sea sediment. The structures of compounds 1–16 were elucidated through comprehensive NMR spectroscopic and specific optical rotation (OR) data analyses. Compound 6 showed antibacterial activity against Pseudomonas fulva with an MIC value of 50 µg/mL. This is the first study to discover a pyridinium derivative and cyclic dipeptides from B. licheniformis.